The vaginal isolate Lactobacillus paracasei LPC-S01 (DSM 26760) is suitable for oral administration - Balzaretti, Silvia; Taverniti, Valentina; Rondini, Greta; Marcolegio, Giorgio; Minuzzo, Mario; Remagni, Maria Chiara; Fiore, Walter; Arioli, Stefania; Guglielmetti, Simone (Frontiers in Microbiology, 2015)
Bacterial vaginosis is one of the most common urogenital diseases affecting women in reproductive age. The administration of probiotics as vaginal suppository has been proposed as a strategy to cure this condition and reduce its recurrence. Nonetheless, also oral consumption of probiotics, which is a more practical route of administration, proved to be an efficient strategy. In this perspective, we studied Lactobacillus paracasei LPC-S01 (DSM 26760), a human vaginal isolate included in commercial probiotic preparations for topical use, in order to assess if this bacterium can also perform as gastrointestinal probiotic. Comparative genomics revealed the presence of several accessory genes suggesting that LPC-S01 is a niche-generalist member of its species. According to a procedure conventionally used to predict the probiotic potential, we demonstrated that the probiotic properties of strain LPC-S01 are equal (e.g., bile tolerance and reduction of NF-κB activation in Caco-2 cells) or superior (e.g., tolerance to gastric juice and adhesion to Caco-2 epithelial cells) to those of the well-known probiotic reference L. paracasei Shirota. We then demonstrated that LPC-S01 is susceptible to antibiotics indicated by EFSA and does not produce biogenic amines. Finally, a double-blind cross-over pilot intervention trial on healthy human volunteers showed that, after a 7-days oral consumption of capsules containing about 24 billion live cells, the fecal cell concentrations of strains LPC-S01 and DG (evaluated by qPCR) were not dissimilar. Specifically, both probiotics’ cell concentrations were above the detection limit for an average of 5 days from the end of the treatment, corresponding to a mean number of evacuations of 7 ± 2. Taken together, these data demonstrate that the vaginal isolate L. paracasei LPC-S01 possesses safety and functional properties that may support its use as probiotic to be administered per os for potential intestinal as well as vaginal applications.